Paradoks Media Sebagai Pilar Keempat Demokrasi - Nyarwi, - (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
Mass media has important role as the fourth pillar in Indonesian democracy system. Media liberalization in post New Order era is aimed to strengthen democracy in Indonesia. However, mass media in post New Order era is in paradoxical situation. This paper examines four important factors related to the role and the position of media in post New Order era. First, it explores the mass media in the arena contestation of interest. Second, it explores the politics of media in the post New Order era. Third, it explains the metamorphosis model of politics. Fourth, it emphasizes the importance of media existence as the fourth pillar of democracy. Furthermore, it argues the strengthening of power-oriented model makes the media paradoxical as the fourth pillar of democracy